Sustainability Management and Financial Performance: An Analysis of the Impact of ESG (Environmental, Social, Governance) Implementation on Profitability and Company Value in Emerging Markets - Tata Putri Salsabila; Intan Septiana Hadi; Muhammad Esa Saputro Priyono (Smart International Management Journal, 2025)
This study analyzes the impact of ESG implementation on financial performance and firm value in emerging markets. Using data from 150 listed companies (2017–2023) and multiple linear regression, ESG scores were linked to profitability (ROA, ROE) and firm value (Tobin’s Q). The results indicate a positive and statistically significant relationship between ESG implementation and financial performance, with the environmental dimension showing the strongest influence. Social and governance aspects showed weaker but positive effects. ESG impact is stronger in larger, low-leverage firms. The findings suggest that tailored ESG integration enhances financial outcomes and resilience, offering insights for sustainable business strategies in emerging economies.